The Influence of Gender Differences on Academic Abilities of Biology Education Students in the Animal Structure Practicum - Maspupah, Meti; Hidayah, Nurul; Ramdhan, Rifki (Bioedunis Journal, 2024)
Differences in the academic abilities of each student are one of the factors that influence the high and low test scores of each student, especially in animal structure practical courses. This research aims to determine the effect of gender differences on the academic abilities of biology education students based on the results of mid-semester exams. The population in this study was all students in the third semester of biology education with a sample of 20 male students and 20 female students. The data collection technique in this research uses a study of students' midterm exam documents which are analyzed using average calculations and followed by statistical analysis in the form of normality tests, homogeneity tests, and continued with hypothesis testing. The average score of male students is 46.5, lower than that of female students, which is 66.5 with the asmp normality test. Sig 0.000 0.05 where the data is not normally distributed. The homogeneity test results obtained asymp value. Sig 0.978 0.05 where the data is homogeneous, and the results of the asmp hypothesis test. Sig (2-tailed) 0.001 0.05 where the hypothesis is accepted. Thus, there is a difference in academic abilities between men and women in the animal structure practicum course, the concept of observing animal tissue.